Experimental photography: concept, poetics and aesthetics of political agency in Latin American art - Carvalho, Ludimilla (Brazilian Journal of Latin American Studies, 2023)
Experimental photography by some Latin American artists shows an affinity with the criticism made by intellectuals on the continent (MIGNOLO, 2010; QUIJANO, 1992; BAIO, 2022; MACHADO, 1984) of the social, epistemic and aesthetic effects of modern European thought. Since the 19th century, photography and its dominant uses have referred to the values of this thinking, such as linear time, objectivity, realism and verisimilitude. Experimental practices, carried out since the 19th century, represent a counterpoint to these values, presenting themselves as an aesthetic and conceptual affront to this epistemological agenda. Without an ordered chronology and characterized by different methodologies and aesthetics, they have been conceptualized with more emphasis since the 2000s, by authors such as Fernandes Junior (2002), Lenot (2017) and Chiarelli (2006). Based on recent research Wanderlei (2021, 2022) and Cruz e Wanderlei (2023), we present the hypothesis that in the Latin American context some experimental works can have a political connotation, as they criticize the historical consequences of Western European Modernity, which we will see from the analysis of the projects Atlântico Vermelho (2017), by Rosana Paulino, and Rumiantes (2022), by Manuel Limay Incil.